The Effectiveness of Think-Talk-Write (TTW) Learning Strategy In Term of Critical Thinking and Mathematical Communication - Muhammad Farid Nasrulloh; Fitri Umardiyah (Jurnal Mercumatika: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2020)
This study aims to describe the effectiveness of Think-Talk-Write (TTW) learning strategy and the conventional learning approach in term of the Critical Thinking and mathematical communication. Compare the effectiveness of Think-Talk-Write (TTW) learning strategy and the conventional learning approach in term of the Critical Thinking and mathematical communication. The population comprised the X student distributed in three class of MA Bahrul Ulum Jombang. The selected sample consisted of Class X-IIS-1 as the class experimental group and Class X-IIS-2 as the class control. The data was analyzed using one-sampel t-test, MANOVA test with T2 Hotteling’s Formula and t-test with Bonferroni criteria. The results of the study: at the 95% level of significance, the mathematics teaching through the Think-Talk-Write (TTW) learning strategy is effective and the conventional learning is not effectice in terms of the Critical Thinking and mathematical communication. The application of through the Think-Talk-Write (TTW) learning strategy is more effective than the conventional learning.